Why Digital Learning is the Key to the Future of Education - Arifudin, Opan (Lafadz Jaya Publisher, 2025)
Digital learning has emerged as a transformative force in the field of education, enabling access to knowledge and skills in ways that were once unimaginable. With the rapid advancement of technology, digital learning is increasingly recognized as the key to the future of education, offering an innovative approach to meet the demands of 21st-century learners. This article examines why digital learning is pivotal to the future of education, focusing on its potential to enhance accessibility, improve personalized learning experiences, and foster lifelong learning. By exploring various digital tools and platforms such as e-learning, MOOCs, mobile apps, and virtual classrooms, the article highlights how digital learning can bridge geographical, economic, and social barriers to education. Additionally, it discusses the benefits of digital learning in enhancing student engagement, supporting diverse learning styles, and providing flexible learning opportunities that cater to individual needs. Despite its promise, the article also addresses the challenges associated with digital learning, such as the digital divide, lack of infrastructure, and the need for digital literacy. Finally, it outlines the importance of adopting policies that support the growth and sustainability of digital learning in the educational ecosystem.